Penggunaan Website 10Fastfingers untuk Melatih Kemampuan Mengetik Siswa MTS Darul Muslim di Desa Tarikolot, Bogor - Yusrizal, Navis; Alfiyah, Khansa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Typing training on the computer is intended to determine the average WPS (Word Per Minute) of students, to encourage students to type quickly and accurately, and also to introduce the importance of typing today. Typing training for students of MTs Darul Muslim is carried out using the SL (Service Learning) method. This activity is carried out with one meeting and is carried out with two sessions in August 2024. This activity includes material and practice sessions. The material session is filled with an introduction to ICT, the importance of typing, ten-finger typing tricks, and questions and answers. Followed by a typing practice session with the 10Fast Fingers website. The results of this training activity were successful. This success aims to increase students' knowledge, namely that technology is not just mobile games, cellphones, and also knowing the importance of fast and accurate typing skills. In addition, the average WPS (Word Per Minute) of each 7th grade student of Mts. Darul Muslim is around 5-10, which means that there needs to be an evaluation and emphasis on typing training for students.